High catalytic nickel-platinum nanozyme enhancing colorimetric detection of Salmonella Typhimurium in milk - Jie Zhu; Lingyue Xu; Junlin Zhang; Yuxin Wang; Hongyue Yu; Chuanchuan Hao; Guohui Cheng; Daofeng Liu; Minghui Chen (Journal of Dairy Science, 2024)
ABSTRACT: Colorimetric qualitative and sensitive quantitative detection of Salmonella Typhimurium holds significant importance for ensuring food safety and preventing foodborne illnesses. In this study, an ultra-high catalytic activity and biocompatible nickel-platinum nanoparticle (NiPt NP) nanozyme is successful synthesized to prepare a nanozyme-linked immunosorbent assay (NLISA) strategy for the detection of Salmonella Typhimurium. The synthesized NiPt NP exhibit high oxidase-like catalytic efficiency, with a Michaelis-Menten constant of 0.493 mM, similar to that of natural horseradish peroxidase (HRP). The maximal reaction velocity was determined to be 1.97 × 10−7 M·s−1, 1.97-fold higher than that of the HRP (1.0 × 10−7 M·s−1). Meanwhile, the antibody employed in this NiPt NP-based NLISA exhibits exceptional capture efficacy, generating a stable immune complex with Salmonella Typhimurium. The NiPt NP-based NLISA demonstrates sensitivity, specificity, convenience, and cost-efficiency for the detection of Salmonella Typhimurium. Under optimal conditions, this NiPt NP-based NLISA demonstrates a quantitative range of 103∼106 cfu/mL with a detection limit as low as 103 cfu/mL. A single-blind experimental testing detects different concentrations of Salmonella Typhimurium-spiked skim milk, indicating the application potential of the proposed NLISA in real samples. In all, this research provides novel insights into the synthesis of nanozymes with excellent catalytic activity and their applications in Salmonella Typhimurium biosensing.